Antibiotic resistance patterns among bacterial pathogens isolated from bloodstream infections at the Maternal and Child Health Hospital, Kumasi, Ghana - Yanchumba, Eric; Deku, John Gameli; Bedzina, Israel; Mensah, Lydia Kessewah; Ablordey, Kenneth; Banahene, Korsah Kwabena; Sey, Cosmos; sar Kennedy, Kaizah; Mensah, Priscilla Osei; Afeke, Innocent; Duedu, Kwabena Obeng (Frontiers in Bacteriology, 2026)
BackgroundBloodstream infections remain a major public health concern globally and are increasingly associated with multidrug-resistant bacterial pathogens. Limited data on antimicrobial resistance patterns among bloodstream isolates in Ghana hinder appropriate empirical therapy, particularly in maternal and child health settings. The study aimed to assess the prevalence, bacterial causes, and antibiotic resistance patterns of bloodstream infections, including multidrug resistance, extensively drug-resistance, pandrug-resistance, extended-spectrum β-Lactamase and carbapenemase-producing pathogens, and their association with patient demographics at the Maternal and Child Health Hospital, Kumasi, Ghana.MethodologyA hospital-based cross-sectional study was conducted from July to September 2025 at the Maternal and Child Health Hospital. Blood samples were collected from 229 suspected bloodstream infection patients referred for culturing and susceptibility testing, and were cultured using the BD BACTEC automated system. Isolates were identified and tested for antibiotic susceptibility using the Phoenix BD BACTEC automated machine. Data were analysed using Stata version 15, applying descriptive and logistic regression analyses with significance set at p<0.05.ResultsOut of 229 participants, 61.6% had positive blood cultures. Among the Gram negatives, Escherichia coli (22.7%) and Klebsiella species (13.5%) were the predominant isolates. Coagulase-negative staphylococci (16.3%) and Staphylococcus aureus (14.9%) were the major Gram-positive causing bloodstream infections. The highest resistance was recorded against cefazolin (54.6%) and ceftriaxone (45.4%), while amikacin (3.5%) and daptomycin (4.3%) showed the greatest efficacy. ESBL and carbapenemase production among the Gram-negative isolates were observed in 27.2% and 12.0% of isolates, respectively. Overall, 96.5% of isolates exhibited some form of resistance, with 81.6% classified as multidrug resistant, 8.5% as extensively drug-resistant, and 5.0% as pandrug-resistant. Longer hospital stays significantly increased infection risk (aPR=2.86; 95% CI: 1.92–4.27; p<0.001).ConclusionThe high prevalence of multidrug resistant bloodstream pathogens at the Maternal and Child Health Hospital, particularly Staphylococcus and Escherichia coli, underscores the urgent need for enhanced infection prevention, antimicrobial stewardship, and periodic surveillance of resistance patterns to guide effective empirical therapy.